UPAYA PENINGKATAN KAPASITAS USAHA MIKRO “NASI UDUK KAK UWIR“ MELALUI RE-BRANDING, RE-PACKING, DAN RE-PROMOTING - Abdul Rachman; Arie Haura; Karmila Firdaus; Muhammad Fadilah; Muhammad Khairurredha; Idha Azizah (Universitas Mataram, 2022)
Crisis conditions caused by Coronavirus Disease 2019 (Covid-19) which spread widely to the Tangerang area. Various policies to prevent the spread of COVID-19 actually have bad implications for various other sectors, especially in the economic sector. The Covid-19 pandemic has made everything that was originally done offline/offline now turns into an online/online system, including the business activities carried out by the UKM